2013
DOI: 10.1186/1471-2393-13-240
|View full text |Cite
|
Sign up to set email alerts
|

Risk of future cardiovascular disease in women with prior preeclampsia: a focus group study

Abstract: BackgroundA history of preeclampsia is a risk factor for the future development of hypertension and cardiovascular disease (CVD). The objective of this study was to assess, in women with prior preeclampsia, the level of knowledge regarding the link between preeclampsia and CVD, motivators for and barriers to lifestyle change and interest in a lifestyle modification program to decrease CVD risk following a pregnancy complicated by preeclampsia.MethodsTwenty women with a history of preeclampsia participated in 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 16 publications
11
72
0
1
Order By: Relevance
“…Women were invited to participate in a 90-minute phone-based focus group, as it has been shown that face-to-face focus groups are difficult for postpartum women to attend [7] and based on our prior experience with a similar population [6]. The use of phone-based focus groups also allowed us to recruit nationwide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women were invited to participate in a 90-minute phone-based focus group, as it has been shown that face-to-face focus groups are difficult for postpartum women to attend [7] and based on our prior experience with a similar population [6]. The use of phone-based focus groups also allowed us to recruit nationwide.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the association between a history of preeclampsia and future hypertension and CVD, the American Heart Association (AHA) updated its recommendations for women in 2011, adding history of preeclampsia to the list of previously established risk factors for CVD (such as active smoking, hypertension or dyslipidemia) [5] and recommend lifestyle modification for women with this history. We previously demonstrated that women with a history of preeclampsia, on average 18 months postpartum, were generally unaware of the link between preeclampsia and future CVD; but once aware of the link, were interested in engaging in lifestyle modification to reduce this risk [6]. The purpose of the present focus groups was to identify specific barriers to learning about the link between a history of preeclampsia and future CVD risk, and to identify barriers to implementing and sustaining recommended healthy lifestyle changes to reduce the risk.…”
Section: Introductionmentioning
confidence: 99%
“…In a focus group study, women with previous preeclampsia were found to be generally unaware of their increased risk of future cardiovascular diseases but were motivated to undertake lifestyle modifications to reduce risk. 50 In view of the burden and impact of cardiovascular disease on women in our society, we recommend a detailed cost-benefit analysis to determine the postnatal timing for a screening program in this high-risk population.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory diagnosis of the respondents which revealed increased proteinuria (48%), reduced urine output (26%), thrombocytopenia (19%) and impaired liver function (7%) may be adduced to the presence of biomolecules normally associated with pregnancy-induced hypertension/eclampsia (Mehta et al, 2015), which are potent risk factors. Clinical complications experienced by respondents which included 39% convulsion, 24% pulmonary edema, 20% kidney failure, 17% liver failure are indications of cardiovascular implications of preeclampsia/eclampsia (Seely et al, 2013;Burgess and Founds, 2016).…”
Section: Discussionmentioning
confidence: 99%